Interactive Counseling Skills Method to Improve Parental Compliance and Self-Efficacy in Child Tuberculosis Prevention Therapy: A Mixed Methods Study - Sari, Ethyca; Siagian, Martha Lowarni; Aprilia, Devi (Journal of Applied Nursing and Health, 2025)
Background: Tuberculosis (TB) is transmitted through saliva droplets containing Mycobacterium tuberculosis. TB Preventive Therapy (TPT) is provided to individuals infected with M. tuberculosis who do not show symptoms of active disease, particularly as part of a child contact investigation. The success of TPT largely depends on parental self-efficacy and adherence in supporting their children throughout therapy. The Interactive Counseling Skills (ICS) strategy is proposed to strengthen these factors. The aim is to examine the effect of ICS on parents’ self-efficacy and adherence in accompanying their children during TPT.. Methods: This study used a mixed-methods approach with quantitative and qualitative data, applying a sequential explanatory design. Sampling was conducted using a quasi-experimental method with a total of 60 participants divided into intervention and control groups. Instruments used included questionnaires and interview guides, with validity tested through Cronbach’s Alpha and triangulation. Data analysis was conducted using the Paired T-Test/Wilcoxon test and thematic analysis. Results: The findings showed a significant increase in parental self-efficacy (p = 0.001) and treatment adherence (p = 0.002) in the intervention group compared to the control group. Qualitative findings supported the quantitative results, with parents in the intervention group stating that the interactive counseling sessions provided them with a better understanding of TB, increased their confidence in supporting the therapy process, and helped them understand the importance of regular TPT administration after attending the ICS sessions. Conclusion: This study demonstrates strong convergence, where the parents’ experiential narratives reinforce significant statistical data. The intervention not only increased self-efficacy and adherence rates but also fostered changes in attitude, understanding, and confidence. It is necessary to develop ICS training modules for healthcare workers so that this intervention can be implemented sustainably and consistently within family-based health services